Model Meningkatkan Kemandirian Pasien Pasca Stroke - Serlina Sandi; Asrijal Bakri (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2021)
Introduction; stroke is a cause of disability so that patients experience limitations in fulfilling daily living activities (ADL). Destination; developed a physical exercise model ROM to increase the independence of post-stroke patients in compliance. Method; quasi-experimental research using the one group pre and post-test design method. The sampling technique was nonprobability sampling with a consecutive sampling approach with a sample size of 18 post-stroke patients. The assessment of independence in compliance with ADL using the Bartel Index was carried out before the ROM intervention and at the end of the ROM intervention. Analysis of the effect of ROM on the independence of ADL compliance with the Wilcoxon Test. Results; showed that there was an effect of the ROM physical exercise model on the independence of post-stroke patients (p = 0.000). There was an increase in the mean independence of respondents after being given ROM physical training (44.4 ± 22.2 to 59.4 ± 16.1). Conclusion; ROM physical exercise model can increase the independence of post-stroke patients in fulfilling daily functional activities